The law of sustainable urban development, urban renewal and urban regeneration in Peru: reflections and contributions - Castillo-García, Rodolfo Francisco (2024)
In Peru, from 1991 to the present, have been approved some regulations and plans related to “urban renewal”, “reurbanization”, and “urban regeneration”. The Law of Sustainable Urban Development N° 31313 in Peru, approved in July 2021, aims to establish the principles, instruments and standards that regulate territorial conditioning, urban planning, and management of urban land, in order to achieve sustainable urban development. This law defines “urban renewal or regeneration”, but does not make a conceptual or normative differentiation between “urban renewal” and “urban regeneration”, and does not make a mention “redevelopment”. In this context, the objective of this article is to reflect and distinguish between “urban renewal” and “urban regeneration”, and propose some conceptual and regulatory contributions so that terms are distinguished and adequately regulated for their operational application.